Functional biogeography and host specificity of bacterial communities associated with the Marine Green Alga Ulva spp. Issue 8 (13th March 2018) - Roth‐Schulze, Alexandra J.; Pintado, José; Zozaya‐Valdés, Enrique; Cremades, Javier; Ruiz, Patricia; Kjelleberg, Staffan; Thomas, Torsten
Abstract: Bacterial communities play an essential role for the function of marine macroalgae. Recent work has shown that bacterial communities associated with individual macroalgae possess on a local scale a functional core that is likely derived from diverse members of functional guilds. It is not known whether such functional cores also exist across large spatial scales or between closely related host species. To address this, we studied here the bacterial communities on three species of the green macroalgal genus Ulva from different geographic locations. While the taxonomic composition was too variable to describe a community core, we identified genes that were enriched across all Ulva samples as compared to the communities of the surrounding seawater. Of these core functions, 70% were consistently found and independent of the Ulva species and biogeography, while the remaining functions ( 30%) are possibly involved in local or host‐specific adaptations. For each host individual, the core functions are provided by bacteria with distinct phylogenetic origin and these bacteria could constitute a global guild of Ulva ‐associated bacteria. Together, our results demonstrate the presence of a stable core set of functional genes in the bacterial communities associated with closely related host species and across large biogeographies.